Arbeitsvorgänge in Bibliotheken: 2. Wissenschaftliche Bibliotheken (AVWB) und Staatliche Bücherei- und Bibliotheksfachstellen (AVBF) (De Gruyter, 2024)
The new standard work for creating job descriptions and job evaluations comprehensively lists new and updated work procedures in academic libraries. The fulfilled job characteristics as well as associated remuneration groups are recorded according to of the currently valid remuneration regulations. The work is supplemented by basic knowledge on the subject of grouping, job description and job evaluation.